Radiographic study of alveolar bone profiles of chronic periodontitis patients: Study descriptive - Hidayat, Muhammad Firman; Pudjiastuti, Peni; supriyadi, Supriyadi (Padjadjaran Journal of Dental Researchers and Students, 2023)
ABSTRACTIntroduction: Chronic periodontitis is a common periodontal disease; prevalence at the age of over 35 years above 75%. Chronic periodontitis is often assessed by the presence of bone loss, namely by the degree of alveolar bone loss and the bone loss pattern. The bone loss profile is very important for assessing periodontitis associated with treatment and treatment planning. This study aims to determine alveolar bone profiles in chronic periodontitis patients. Methods: This descriptive study used periapical radiograph samples from patients with a diagnosis of chronic periodontitis at Dental Hospital, University of Jember in November to December 2022 which were taken using a total sampling technique. Bone loss is determined by measuring the distance from the point CEJ-ABC on the radiograph using a caliper. The pattern of bone loss was visualized and classified into vertical and horizontal patterns. Results: The percentage of horizontal bone loss patterns is 92% and 8% vertical. The average bone loss in males is greater than in females by 1.16mm, bone loss in the maxillary bone is greater than that of the mandible by 1.04mm, the largest bone loss is in the maxillary incisors by 2mm. Conclusion: There are more horizontal bone loss patterns than vertical ones. Bone loss in men is greater than in women. The maxillary teeth have a greater average bone loss than the mandible. Upper incisors show the greatest bone loss compared to other regions.KEY WORDS: alveolar bone, chronic periodontitis, periapical radiograph, bone loss, bone loss patternRadiografi profil kehilangan tulang alveolar pada pasien periodontitis kronis: studi deskriptifABSTRAKPendahuluan: Periodontitis kronis merupakan penyakit periodontal yang umum terjadi prevalensinya pada usia diatas 35 tahun dengan persentase hingga 75%. Periodontitis kronis sering dinilai dari adanya kehilangan tulang alveolar (bone loss), yaitu tingkat kehilangan tulang alveolar dan pola kerusakannya. Profil bone loss sangat penting untuk penilaian periodontitis yang dikaitkan dengan rencana perawatan dan perawatan. Penelitian ini bertujuan mengetahui profil kehilangan tulang alveolar pada pasien periodontitis kronis. Metode: Penelitian deskriptif ini menggunakan sampel radiografi periapikal dari pasien dengan diagnosis periodontitis kronis  di Rumah Sakit Gigi dan Mulut Universitas Jember pada bulan November-Desember 2022 yang diambil menggunakan  teknik total sampling yang memenuhi kriteria. Pengukuran bone loss dilakukan dengan cara menentukan titik cemento enamel junction (CEJ) - alveolar bone crest (ABC) pada radiografi menggunakan jangka sorong. Pengamatan pola kerusakan tulang alveolar dilakukan secara visual dan diklasifikasikan menjadi pola kerusakan vertikal dan horizontal. Hasil: Pola kerusakan alveolar crest horizontal 92% dan vertikal 8%. Rerata bone loss   pada laki-laki lebih besar dibandingkan dengan perempuan sebesar 1,16mm, bone loss pada rahang atas lebih besar dibandingkan dengan rahang bawah sebesar 1,04mm, bone loss terbesar adalah pada gigi insisivus rahang atas sebesar 2mm. Simpulan: Pola bone loss horizontal lebih banyak dibandingkan vertikal. Bone loss pada laki-laki lebih besar dibandingkan perempuan. Geligi rahang atas memiliki rerata bone loss yang lebih besar dibandingkan dengan rahang bawah. Gigi insisivus rahang atas menunjukkan rerata bone loss terbesar dibandingkan dengan regio lainnya.KATA KUNCI: tulang alveolar, periodontitis kronis, radiografi periapikal, bone loss, pola kerusakan.